Sub-Minimum Inhibitory Concentrations of Rhubarb Water Extracts Inhibit Streptococcus suis Biofilm Formation - Ding, Wen-Ya; Li, Yan-Hua; Lian, He; Ai, Xiao-Yu; Zhao, Yu-Lin; Yang, Yan-Bei; Han, Qiang; Liu, Xin; Chen, Xue-Ying; He, Zhonggui (Frontiers in Pharmacology, 2017)
Abstract: Streptococcus suis is one of the most important swine pathogens, which can cause persistent infection by forming biofilms. In this study, sub-minimum inhibitory concentration (sub-MIC) of rhubarb water extracts were found to inhibit biofilm formation. Two-component signal transduction systems (TCSs), transcriptional regulators, and DNA binding proteins were compared under two conditions: 1) cells treated with sub-MIC rhubarb water extracts and 2) untreated cells. Using an isobaric tags for relative and absolute quantitation ( iTRAQ) strategy, we found that TCSs constituent proteins of histidine kinase (HK) and response regulator (RR) were significantly down-regulated. This down-regulation can affect the transfer of information during biofilm formation. The transcriptional regulators and DNA binding proteins that can interact with TCSs and interrupt gene transcription were also significantly altered. For these reasons, the levels of protein expressions varied in different parts of the treated versus untreated cells. In summary, rhubarb water extracts might serve as potential inhibitor for the control of S. suis biofilm formation. The change in TCSs, transcriptional regulators, and DNA binding proteins may be important factors in S. suis biofilm inhibition.